PENGARUH SISTEM PENILAIAN KINERJA TERHADAP LOYALITAS PEGAWAI DENGAN PERSEPSI KEADILAN ORGANISASI SEBAGAI VARIABEL MODERASI DI DINAS KOPERASI DAN UKM KABUPATEN MUSI RAWAS - Marliza Okta Diani; Suyadi; Yuli Eprianti (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the effect of performance appraisal system on employee loyalty with perceived organizational justice as a moderating variable. The study used a quantitative approach with a survey method. Data were collected through distributing questionnaires to 50 employees of the Cooperative and SME Office of Musi Rawas Regency and analyzed using Partial Least Square (PLS) with SmartPLS 3 program. The results showed that work loyalty had a positive and significant effect on employee performance with a t-statistic value of 5.978 > t-table value of 1.681 and P-Value of 0.000 < α = 0.05. Organizational justice had no significant effect on employee performance with a t-statistic value of 0.197 < t-table value of 1.681 and P-Value of 0.844 > 0.05. Organizational justice perception as a moderating variable proved to strengthen the effect of loyalty on employee performance. The R-Square value of 0.683 indicated that 68.3% of the variation in employee performance could be explained by loyalty and organizational justice variables